ALGUNAS CARACTERÍSTICAS DEL SECTOR TRANSPORTE EN COSTA RICA Y SU INFLUENCIA EN EL CONSUMO DE HIDROCARBUROS, 1965-2004 - D’Alolio Sánchez, Ileana (2011)
This article describes a series of characteristics pertaining to the transportation sector in Costa Rica, as well as the country’s vehicle fleet, highlighting the impact caused by the specificities of land transportation on the fuel consumption structure at the domestic level, thus showing the increasing dependence on hydrocarbon fuel consumption. Finally, the author concludes that in Costa Rica the use of fossil fuel as an energy source is irrational and inefficient, since it depends on individual means of land transportation, which causes great stress on the socioeconomic structure, as well as on the environment.